Patient and provider experiences with relationship, information, and management continuity - Jeanette Jackson; Gail MacKean; Tim Cooke; Markus Lahtinen (The Beryl Institute, 2017)
From 2003 to 2014, the Health Quality Council of Alberta (HQCA) monitored patient experiences with healthcare services through a biennial Satisfaction and Experience with Healthcare Services (SEHCS) survey. The findings consistently showed a direct link between coordination of care, an aspect of continuity of care, and healthcare outcomes. Specifically, it showed that better coordination is linked to positive outcomes; the reverse is also true. Given the critical role continuity of care plays in the healthcare system, the HQCA conducted in-depth interviews, interactive feedback sessions and focus groups with patients and providers to explore factors that influence both seamless and fragmented patient journeys. Continuity of care refers to "the degree to which a series of discrete healthcare events is experienced as coherent and connected and consistent with the patient's healthcare needs and personal context". Reviews of international literature have identified three major subtypes of continuity across healthcare settings: relationship, information, and management continuity. This study showed that from the patient perspective, relationship continuity is most valued and is foundational for experiencing information and management continuity. A trusting, patient-centred, and respectful relationship with a primary healthcare provider is central to this. From the provider perspective, information continuity is most important. Primary care providers get frustrated if information is withheld or delayed, and if other providers change treatment plans or medications. Patients highly value timely access to their own information. They also value having enough time during an appointment with a family doctor who listens and communicates effectively. Both patients and providers value and benefit from management continuity, which was described by many as a partnership or shared responsibility for managing and coordinating healthcare services. Future conversations about health system design should focus on how all providers and services can work together, and engage patients, to co-design a system that is built around patient-centred relationships.